Successful Treatment of Severe Generalized Tetanus with Refractory Spasm and Pneumonia Co-Infection: a Case Report - Komang Yunita Wiryaning Putri; Ichlasul Mahdi Fardhani; Muhammad Isra Rafidin Rayyan (Journal of Agromedicine and Medical Sciences, 2024)
Background: Tetanus is a high mortality rate infectious disease caused by Clostridium tetani. Although it can be prevented through vaccination, tetanus remains a significant problem, especially in developing countries, so comprehensive management is needed to prevent more fatal complications. Case report: A 52-year-old patient was diagnosed with tetanus due to exposure to tree thorns and experienced muscle spasms and jaw stiffness that could not be controlled with benzodiazepine agents alone. The patient was treated for more than 30 days in the intensive care unit with mechanical ventilation, immunoglobulin, antibiotics, antispasms, and sedatives. Patients experience autonomic dysfunction, causing bradycardia, tachycardia, and fluctuating blood pressure. In addition, the patient was also infected with Pseudomonas aeruginosa pneumonia during the treatment period. Finally, the patient was successfully treated and removed. Conclusion: This case report highlights the importance of multidisciplinary ICU care in diagnosis and therapy, which is expected to provide the best patient outcomes. Keywords: Generalized tetanus; refractory spasms; pneumonia; neuroinfectious disease